Comportamento ético nas organizações, a partir da percepção de alunos de uma escola de negócios - Martins, Jonatas Guilherme da Silva (Universidade do Vale do Rio dos Sinos, 2019)
The present study has aimed on analyzing the ethical perception by students from a Business School at a private University in Southern Brazil. The research has been conducted in two phases: one quantitative and one qualitative. The sample has been composed by students at the undergraduate level, both lato and stricto sensu. The participants have answered the Perception Scale of Organizational Ethic Behaviors (EPCEO – Gomide et al, 2003), along with a new instrument, in order to be able to examine students’ perception regarding the Higher Education Institution (HEI) where they study, besides the social-demographic data which contribute for the multivariated statistic analysis proposed by such study. Among the main results, we have identified relevant issues, such as the need by the collaborators of being part of the company decision taking, as well as the perception by the strictu sensu students regarding the participation on social projects, in which a lower result compared to the other levels of graduation evaluated has been identified. Along with that, other issues were risen by such group regarding its organizations, both company or educational.
Keywords: Ética; Ética Empresarial; Ética Educacional; Percepção Ética; Ethics; Business ethics; Educational ethics; Ethical perception; ACCNPQ::Ciências Sociais Aplicadas::Administração